2019
DOI: 10.1016/j.vaccine.2019.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen seroprevalence among pre- and post-vaccine cohorts in Cambodia, 2017

Abstract: Highlights This study proved of Cambodia achieving WHO 2017 target of <1% HBsAg prevalence. HBsAg prevalence in 5–7 years old children was 0.56% (95%CI: 0.32%–0.98%). HBsAg prevalence among the mothers was 4.39% (3.53%–5.45%). Among children with HBsAg-positive mother, prevalence was as high as 10.11%. 78.4% of children received HepB birth-dose and 58.7% were administered ≤24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 7 publications
3
30
0
Order By: Relevance
“…Here by this study, the rate of mother-to-child transmission of HBV infection showed very low percentage (< 1%) which indirectly proves the effectiveness of hepatitis B vaccination to all infant as national immunization program in Burkina Faso. The similar study in Cambodia also showed the effectiveness of hepatitis B vaccination including hepatitis B birth dose vaccine within 24 h after delivery which significantly reduce HBsAg prevalence to less than 1% in post-vaccine cohort of 5-7 years old children [31].…”
Section: Discussionmentioning
confidence: 63%
“…Here by this study, the rate of mother-to-child transmission of HBV infection showed very low percentage (< 1%) which indirectly proves the effectiveness of hepatitis B vaccination to all infant as national immunization program in Burkina Faso. The similar study in Cambodia also showed the effectiveness of hepatitis B vaccination including hepatitis B birth dose vaccine within 24 h after delivery which significantly reduce HBsAg prevalence to less than 1% in post-vaccine cohort of 5-7 years old children [31].…”
Section: Discussionmentioning
confidence: 63%
“…Types of DBS used in this study. HemaSpot samples, all of them were initially screened and confirmed by WHO standard Rapid point of care HBsAg test, were collected using DBS(HemaSpot) and venipuncture from 5-6 years-old children and their mothers from a nationally representative epidemiological survey conducted in Cambodia in 2017and were used to evaluate the rate of agreement and specificity of DBS 28 . DBS samples were shipped at −80 degrees from Cambodia to Japan by the World Courier.…”
Section: Types Of Hbsag Rapid Point Of Care Test Used In This Studymentioning
confidence: 99%
“…Among 95 HBsAg positive mothers, nine of their children were positive for HBsAg giving MTCT rate of 9.5% (9/95). The detail of background demography were already discussed by Vichit et al [8]. In this study, we present the outcomes from genome sequences analysis.…”
Section: Study Participantsmentioning
confidence: 80%
“…This was the nationwide sero-epidemiological study on HBsAg prevalence among 5-7 years old children and their mothers from 25 provinces of the whole Cambodia in 2017 using the multistage stratified random sampling strategy. Its study designs was introduced previously [8] and results of HBV prevalence from this study had been accepted by WHO Western Pacific Regional Office. Dried blood spot (DBS) using HemaSpot™ (Spot on Science Inc., Austin, USA) samples were collected from 2520 children and their 2028 mothers but two children DBS samples and five mothers' DBS samples were excluded for their insufficient amount of blood for measurement.…”
Section: Subjects Of the Studymentioning
confidence: 99%
See 1 more Smart Citation